“Challenging behavior” in dementia care: ethical complications of a well-intentioned concept - Barth, Jonas (Frontiers in Psychiatry, 2024)
Uncommon behaviours such as aggression, apathy or restlessness are described as challenging behaviours in dementia care. On the one hand, this concept describes a practical problem faced by care staff and, at the same time, defines normatively how care staff should deal with this problem. A frequent benchmark here is the dignity of the person in need of care, which caregivers should also respect in the case of challenging behaviour. However, little is known about the normative standards that are effective in practice in everyday care when dealing with challenging behaviour. Researching these can provide information on which standards are actually applied and encourage reflection on which standards should be applied. In view of the fact that challenging behaviour can also be associated with aggression and/or violence in particular, an ethically significant question arises as to what effects the practical handling of such behaviour has on the extent of the willingness to use violence. The aim of this article is therefore to present empirical findings from an ethnographic study that focuses on the interpretation and practical handling of aggressive behaviour of care recipients by the nursing staff. In essence, it will be shown that a professional approach to challenging behaviour helps to prevent people with dementia in need of care from committing violent acts. If this finding is analysed in terms of its ethical implications, the conclusion suggests itself that the exclusion of the possibility of using violence is to be welcomed, since the exercise of violence makes respect for the dignity of another person, if not impossible, at least more difficult. However, it is questionable whether, under such conditions, the renunciation of violence can still be attributed the freedom required to qualify it as ethically good behaviour.